Pengaruh Body Shaming Terhadap Kesehatan Mental Remaja (International Forum of Researchers and Lecturers, 2024)
The issue of verbal bullying or body shaming is the driving force behind this research. Interview results indicate that some students at SMPN 13 Medan have experienced body shaming. The aim of this research is to understand how body shaming impacts adolescents at SMPN 13 Medan. Physical shaming is also a form of verbal bullying, which means using words to hurt or insult someone. Among teenagers, body shaming has a negative impact on the next generation. This research focuses on the impact of body shaming on adolescents. This research uses a qualitative method with a case study approach. The main objective of this research is to understand how body shaming affects adolescents deeply, physically, mentally and socially. The data collection methods in this research are observation, interviews, documentation, and voice recordings. Additionally, the data analysis methods used in this research are data reduction, data presentation, or information recognition.